Cercyon (Cercyon) unipunctatus - Ryndevich, Sergey K.; Jia, Fenglong; Fikáček, Martin (Zenodo, 2017)
Cercyon ( Cercyon ) unipunctatus (Linnaeus, 1758) (Figs 8, 11, 13) Coccinella unipunctata Linnaeus, 1758: 364. Transferred to Cercyon by LEACH (1817: 95). For complete synonymy see HANSEN (1999). Type locality. Europe. Type material examined. Coccinella unipunctata . The species was described from Europe based on an unspecified number of specimens. Based on the on-line catalogue of the Linnaeus collection, there is a single pinned specimen present in the collection, bearing the labels ‘unipunctata [hw] // 6 [p]’. We consider this specimen as the syntype. Based on the photographs available on-line, the specimen corresponds well with the European specimens treated under the name Cercyon unipunctatus by the body form and coloration (yellow elytra with central dark spot and darkened sutural interval, dark pronotum with pale lateral sides). Additional material examined. KAZAKHSTAN: EAST KAZAKHSTAN REGION: 1 spec. (SZMN): Vost. Kazakhstan, Markakolskiy r-n [Markakol district], s. [vill.] Urunkhayka, korov.n-z [cow dung], Markakolskiy rayon, 2.vii.1996, V. Zinchenko [leg.]. RUSSIA: YAMALO- NENETS AUTONOMOUS OKRUG: 2 spec. (ZMMU): Salekhard, 19.vi.1955, Telishev leg. KEMEROVO OBLAST: 1 spec. (ZISP):‘Kuznetsk, Tomsk g.’, Khvorov & Gorchakovskiy [leg.]. TYUMEN OBLAST: 1 spec. (ZISP): okr. Tobolska [Tobolsk env.], 21.v.1925, Fridolin [leg.]. IRKUTSK OBLAST: 1 spec. (ZISP): Irkutsk, Yakovlev [leg.]. SAKHA (YAKUTIA) REPUBLIC: 4 spec. (ZISP): Yakutsk, 22.v.1911; 1 spec. (ZISP): same locality, 22.vi.[19]25, Bianki [leg.]; 2 spec. (ZISP): same data but 18.vi.[19]25. ALTAI REPUBLIC: 1 spec. (ZISP): Uznezya on Katun, Altai, 25.vii. [1]909, [leg.] Gorchakovskiy; 1 spec. (ZISP): same locality, 4.–6.viii.[1]909. SAKHALIN OBLAST: 1 spec. (CSR): Kunashir, cordon Аlekhinskiy, 7.vii.2015, Yu. Sundukov & L. Sundukova leg. Published records. RUSSIA: PRIMORSKY KRAI: Chernye Gory, Venedivnovo [likely misspelled form of “Venevitinovo”] (HEBAUER 1995). MONGOLIA: KHENTII: Onon-Balj National Park, Bayan-Ovoo (KORSUN et al. 2012). CHINA: ...